Mengukur Social Transfer In Kind (STIK) Dan Kontribusinya Terhadap Pengeluaran Konsumsi Rumah Tanggadi Sulawesi Barat Tahun 2011-2017 - Didiq Rosadi Ali (MediaTrend, 2019)
Disposable income (Disposable Income) is considered not enough anymore to be used to measure and compare the welfare level of a region. This is because the disposable income indicators do not accommodate the effects of social transfers in Kind (STIK) of  goods and services provided by  the  Government and  Non-Profit Institutions Serving for Households (NPISH). Therefore, a growing number of statistical institutions and economists recommend doing STIK calculations and adding them to the portion of household income to create more accurate new income measures. The problem is, the measurement of social transfers (STIK) has not been done much yet and there are no similar research yet conducted in Indonesia. This study aims to (1) provide alternative STIK calculations with the new method of the West Sulawesi Gross Regional Domestic Product (GRDP) component, and (2) Assess the STIK efficiency level in supporting household economies in West Sulawesi. The results of this study indicate that the total value of STIK in West Sulawesi in 2011-2017 ranged from 1.30 to 1.98 trillion rupiah. In addition, districts with STIK highest efficiency levels in providing additional allocations to household consumption expenditures which are calculated through the proportion of STIK to total final household consumption expenditure are Mamuju Regency with a percentage of 18.8 percent.